c-Met activation leads to the establishment of a TGFβ-receptor regulatory network in bladder cancer progression - Sim, W.J.; Iyengar, P.V.; Lama, D.; Lui, S.K.L.; Ng, H.C.; Haviv-Shapira, L.; Domany, E.; Kappei, D.; Tan, T.Z.; Saie, A.; Jaynes, P.W.; Verma, C.S.; et al. (NATURE PUBLISHING GROUP, 2019)
Treatment of muscle-invasive bladder cancer remains a major clinical challenge. Aberrant HGF/c-MET upregulation and activation is frequently observed in bladder cancer correlating with cancer progression and invasion. However, the mechanisms underlying HGF/c-MET-mediated invasion in bladder cancer remains unknown. As part of a negative feedback loop SMAD7 binds to SMURF2 targeting the TGFβ receptor for degradation. Under these conditions, SMAD7 acts as a SMURF2 agonist by disrupting the intramolecular interactions within SMURF2. We demonstrate that HGF stimulates TGFβ signalling through c-SRC-mediated phosphorylation of SMURF2 resulting in loss of SMAD7 binding and enhanced SMURF2 C2-HECT interaction, inhibiting SMURF2 and enhancing TGFβ receptor stabilisation. This upregulation of the TGFβ pathway by HGF leads to TGFβ-mediated EMT and invasion. In vivo we show that TGFβ receptor inhibition prevents bladder cancer invasion. Furthermore, we make a rationale for the use of combinatorial TGFβ and MEK inhibitors for treatment of high-grade non-muscle-invasive bladder cancers.